SCALING RETAIL: UNDERSTANDING LARGE-SCALE DISTRIBUTED SYSTEMS IN MODERN E-COMMERCE - Gaurav Agrawal (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the evolution and implementation of large-scale distributed systems in modern retail environments. It examines the transformation from traditional single-server architectures to sophisticated distributed computing platforms that power contemporary e-commerce operations. The article investigates technical challenges, architectural considerations, and resource implications while highlighting the critical role of microservices, data management, and cloud infrastructure. Through analysis of performance metrics, component integration, and best practices, the article demonstrates how distributed systems have revolutionized retail operations by enabling scalability, reliability, and real-time processing capabilities. The article also addresses the resource implications and implementation strategies necessary for successful deployment of these systems in retail environments.